A study on delivering customer satisfaction who choosing Datai Bay Golf Club Langkawi as golfing destination / Syaril Izam Norrdin - Norrdin, Syaril Izam (1998)
Malaysia has become favourites destination among foreign golfers and yet many resort and golf clubs are able to satisfy sizeable golfers around the world. With this scenario, tourism golf involved in anything that does provide value and satisfaction in the form of golfers enjoyment and profit. Through the research, the researcher studies on delivering customer satisfaction whom choosing Datai Bay Golf Club Langkawi as Golfing Destination. The researcher distributes the questionnaire form to golfers who play at the Club to identify their satisfaction. The analysing techniques that been used is Percentage Techniques and SPSS Program. The result from the research discovered that majority of golfers satisfies with the services offered, facilities provided and the location of Datai Bay Golf Club Langkawi.